Critical Care Resources in Guangdong Province of China: Three Surveys from 2005 to 2015*. Issue 12 (December 2017) - Wu, Jian-Feng; Pei, Fei; Ouyang, Bin; Chen, Juan; Li, Yi-Min; Feng, Yong-Wen; Guo, Fa-Liang; Zhou, Li-Xin; Wang, Zheng; Guo, Ying-Jun; Lin, Qin-Han; Li, Zhan-Peng; et al.
Abstract : Objectives: Data about the critical care resources in China remain scarce. The purpose of this study was to investigate the variation and distribution of critical care resources in Guangdong province from 2005 to 2015. Design: Data in regard to critical care resources were collected through questionnaires and visits every 5 years from 2005. Setting: All hospitals in Guangdong province were screened and hospitals that provide critical care services were enrolled. Intervention: None. Measurements and Main Results: One hundred eleven, 158, and 284 hospitals that provide critical care services were enrolled in the three consecutive surveys respectively. The number of ICUs, ICU beds, intensivists, and nurses increased to 324, 3, 956, 2, 470, and 7, 695, respectively, by 2015. Adjusted by population, the number of ICU beds per 100, 000 (100, 000) population increased by 147.7% from 2005 to 2015, and the number of intensivists and nurses per 100, 000 population increased by 35.3% and 55.1% from 2011 to 2015. However, the numbers in the Pearl River Delta, a richer area, were higher than those in the non–Pearl River Delta area (ICU beds: 4.64 vs 2.58; intensivists: 2.90 vs 1.61; nurses: 9.30 vs 4.71 in 2015). In terms of staff training, only 17.85% of intensivists and 14.29% of nurses have completed a formal accredited critical care training program by 2015. Conclusions: Our study was the first one to investigate the trend and distribution of critical care resources in China. The quantity of ICU beds and staff has been increasing rapidly, but professional training for staff was inadequate. The distribution of critical care resources was unbalanced. Our study can be beneficial for healthcare policymaking and the allocation of critical care resources in Guangdong province and other provinces in China. Abstract : Supplemental Digital Content is available in the text.